Analysis of the effect of polarization traps and shallow impurities on the interlevel light absorption of quantum dots - Boichuk, V.I.; Leshko, R.Ya.; Karpyn, D.S. (Condensed Matter Physics, 2017)
A spherical quantum dot (QD) heterosystem CdS/SiO2 has been studied. Each QD has a hydrogen-like impurity
in its center. Besides that, it has been accounted that a polarization trap for electron exists at the interfaces due
to the difference between the QD and matrix dielectric permittivity. It has been defined that for small QD radii
there are surface electron states. For different radii, partial contributions of the surface states into the electron
energy caused by the electron-ion and electron-polarization charges interaction have been defined. The linear
light absorption coefficient of noninteracting QDs has been calculated taking into account the QD dispersion
by the size. It is shown that the surface states can be observed into different ranges of an electromagnetic
spectrum. У роботi дослiджується наногетеросистема сферичних квантових точок (КТ) CdS у матрицi SiO2. Кожна
КТ у центрi мiстить водневоподiбну домiшку. Крiм того, враховано, що бiля меж подiлу через рiзницю
дiелектричних проникностей виникає поляризацiйна пастка для електрона. Встановлено, що для малих
радiусiв КТ iснують поверхневi електроннi стани. Для рiзних радiусiв КТ обчислено парцiальнi внески в
енергiю зв’язку поверхневих станiв вiд взаємодiї електрона з iоном домiшки та поляризацiйними зарядами. Проведено обчислення коефiцiєнта мiжрiвневого поглинання гетеросистеми з невзаємодiючими КТ,
враховуючи їх дисперсiю за розмiрами. Показано, що поверхневi стани проявляються в рiзних областях
спектру.